Determination of Electric Vehicle Power Consumption for Assorted Pavement Gradient Using Matlab/Simulink - Md .Ruhul Amin; Rajib Baran Roy (Institute of Advanced Engineering and Science, 2014)
Due to less pollution, silence and high efficiency electric vehicles are fascinating to the citizens widely. There are number of physical and electrical aspects are to be considered during vehicle modeling. When electric vehicle runs on the concrete surface rolling resistance resist the vehicle tire to move fast. On the other hand when the vertical angle of vehicle drive is increased or decreased by somewhat degrees the forward force is also increased or decreased respectively. In this paper, a typical electric vehicle dynamic is modeled to mechanical parameter after conversion its mechanical torques, the electrical power is obtained by required mechanical torque and angular velocity of propel as well as wheel. The permanent magnet DC motor is used to simulate the vehicle speed and torque. MATLAB created surface or road gradients are used to investigate torque in different ups and downs at different angle. After analyzing battery error the proportional integral controller gain is derived for achieving desired output from the vehicle.